Proteomic Studies of Cholangiocarcinoma and Hepatocellular Carcinoma Cell Secretomes - Srisomsap, Chantragan (Hindawi Publishing Corporation, 2010)
Cholangiocarcinoma (CCA) and hepatocellular carcinoma (HCC) occur with relatively high incidence in Thailand. The secretome, proteins secreted from cancer cells, are potentially useful as biomarkers of the diseases. Proteomic analysis was performed on the secreted proteins of cholangiocarcinoma (HuCCA-1) and hepatocellular carcinoma (HCC-S102, HepG2, SK-Hep-1, and Alexander) cell lines. The secretomes of the five cancer cell lines were analyzed by SDS-PAGE combined with LC/MS/MS. Sixty-eight proteins were found to be expressed only in HuCCA-1. Examples include neutrophil gelatinase-associated lipocalin (lipocalin 2), laminin 5 beta 3, cathepsin D precursor, desmoplakin, annexin IV variant, and annexin A5. Immunoblotting was used to confirm the presence of lipocalin 2 in conditioned media and cell lysate of 5 cell lines. The results showed that lipocalin 2 was a secreted protein which is expressed only in the conditioned media of the cholangiocarcinoma cell line. Study of lipocalin 2 expression in different types of cancer and normal tissues from cholangiocarcinoma patients showed that lipocalin 2 was expressed only in the cancer tissues. We suggest that lipocalin 2 may be a potential biomarker for cholangiocarcinoma.